Myxoid Liposarcoma of Male Breast - An Unusual Presentation - Kzader, Kazi Manzur; Hossain, AFM Anwar; Hussain, Syed Md Akram; Ali, Md Yakub (Bangladesh Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Myxoid Liposarcoma is the second most common type of Liposarcoma, representing 30-40% of all Liposarcoma in the extremities, particularly the thighs. The more frequent sites of Myxoid Liposarcoma in decreasing order of frequency are the buttocks, retroperitoneum, trunk, ankles, proximal Limb girdle, head and neck, wrist. Myxoid Liposarcoma of male breast is an unusual and rare case of breast malignancy. DOI: 10.3329/bmj.v37i2.3597 Bangladesh Medical Journal 37(2) 2008 68